PENGEMBANGAN KAWASAN PECINAN SEBAGAI KAWASAN WISATAHERITAGE DIKOTA BANDUNG - Novrida Kurnia Sari, - (2012)
Bandung City has one historical place built in late 19th century. This place is called China town, where most ofthe Chinese inheritance, Tionghoa people, live and role their traditions. Today, this China Town has been declared as one of heritage place in Bandung City. Meanwhile, the existence ofChina Town has not yet well-known as heritage place among citizens. To revive the atmosphere China Town in order to support its existence, the development of heritage tourism is expectedto be able topreserve ChinaTowns' heritage objects. The method used in this research is descriptive analysis, which is a research more directed to the disclosure ofthe issue as it is and to reveal thefacts that is exist. Theories pertaining to support the writing are development in tourism, heritage concept, and tourism place development. Interviews with parties concerned to China Town also done to collect actual an accurate data, especially development programs that has beendesigned bygovernmentfor the China Town its self. The research was also supported by a field study and observation conductedto see thefactual condition ofChina Town Bandung. The results showed that the heritage area of Chinatown Bandung has the potential to be developed as a heritage tourist Place. Through the results of research byanalyzing the data collected, it can be recommended that Chinatown heritage site development strategy is to exploit the potential that exists, to revitalize the physical buildings, to buildinfrastructures, to improve the quality of human resources, to build partnerships with the private sector and no less important is to introduce the Chinatown as heritage site to the citizens.